108k views
5 votes
Which of the following correctly simplifies the expression 2 to the power of 3 multiplied by 3 to the power of 0 whole over 5, the whole squared.? (5 points)

2 to the power of 3 multiplied by 1 whole over 5, the whole squared. = 2 to the power of 6 multiplied by 1 squared over 5 squared. = 64 over 25.

2 to the power of 3 multiplied by 1 whole over 5, the whole squared. = 2 to the power of 5 multiplied by 1 squared over 5 cubed. = 32 over 125.

2 to the power of 3 multiplied by 0 whole over 5, the whole squared. = 2 to the power of 6 multiplied by 0 over 5 squared. = 0

2 to the power of 3 multiplied by 0 whole over 5, the whole squared. = 2 to the power of 5 multiplied by 0 over 5 cubed. = 0

2 Answers

3 votes

Answer:

2 to the power of 3 multiplied by 1 whole over 5, the whole squared. = 2 to the power of 6 multiplied by 1 squared over 5 squared. = 64 over 25

User Chris Arguin
by
4.9k points
3 votes

Answer:

2 to the power of 3 multiplied by 1 whole over 5, the whole squared. = 2 to the power of 6 multiplied by 1 squared over 5 squared. = 64 over 25.

Explanation:

TRUST ME IT IS A

User Lonetwin
by
4.4k points